Resist! : The 1960s Protests, Photography & Visual Legacy. - Eyene, Christine; Memou, Antigoni; De Boodt, Kurt; Dujardin, Paul (Brussel : Bozar, 2018)
AES+F ; Akomfrah, John ; Barbey, bruno ; Berry, Ian ; Biemann, Ursula ; Tavares, Paulo ; Brodsky, Marcelo ; Burri, René ; Caron, Gilles ; Depardon, Raymond ; Douglas, stan ; Fatmi, Mounir ; Freed, Leonard ; Gaumy, Jean ; Glinn, Burt ; Hamaya, Hiroshi ; Jantjes, Gavin ; Loskutov, Artem ; Mendel, Gideon ; Ressler, Olivier ; Sacco, Graciela ; Sansour, Larissa ; Schapiro, Steve ; Schulze Eldowy, Gundula ; Serralongue, Bruno ; Storck, Henri ; Mellaerts , Hugo ; Tillmans, Wolfgang ; Williamson, Sue ; Willis, Thomas ; Hank ; Xu, Yong
Resist! The 1960s Protests, Photography & Visual Legacy, Bozar, Brussel, 27 juni tot 26 augustus 2018
boek